Promotion of initial swim bladder inflation and effect of initial inflation failure on skeletal malformation in cultured seven‐band grouper Hyporthodus septemfasciatus (Thunberg). (24th November 2014) - Tsuji, Masaharu; Uji, Susumu; Tsuchihashi, Yasushi; Okada, Kazuhiro; Kawamura, Takeshi; Katoh, Takashi; Kasuya, Tohru; Nigo, Takuo; Hamabe, Atsushi; Miyamoto, Atsushi; Nakamura, Sahoko; Nakano, Akiko; et al.
Abstract: The effects of the removal of the oily surface film on initial swim bladder inflation and survival in cultured seven‐band grouper Hyporthodus septemfasciatus were investigated during the larval stage. Additionally, the relationship between swim bladder inflation failure and malformations in later stages was examined. To explore promotion conditions for inflation, duplicate experiments were conducted under three different water surface conditions: removal of the oily surface film (ROF group), covering the water surface with an oil film (COF group), and sealing the water surface with liquid paraffin (SLP group). Larval swim bladder inflation was first observed 14 days after hatching (DAH) in the ROF group; thereafter, swim bladder inflation rates increased to 11.1% and 38.7% until the end of the experiments. This indicates that initial swim bladder inflation occurs at the pre‐flexion stage in larval development. Conversely, bladder inflation was rarely observed in the COF or SLP groups, indicating the promotional effect of surface film removal on larval swim bladder inflation and suggesting that gulping atmospheric air is necessary for initial inflation. Although larval water surface death occurred frequently in the ROF group, no significant difference existed in any group between the survival rates at 10 DAH and at the end of the experiment. The incidence rate of spinal curvature and deformation of the centra was significantly higher in individuals without initial swim bladder inflation, and these malformations mainly occurred in the caudal vertebra. Therefore, the removal of the oily surface film promotes initial swim bladder inflation and reduces larval malformations.